Impact of web blight on photosynthetic performance of an elite common bean line in the Western Amazon region of Colombia - Suárez, Juan Carlos; Vanegas, José Iván; Anzola, José Alexander; Contreras, Amara Tatiana; Urban, Milan Oldřich; Beebe, Stephen E.; Rao, Idupulapati M. (MDPI, 2022)
Disease stress caused by plant pathogens impacts the functioning of the photosynthetic apparatus, and the symptoms caused by the degree of severity of the disease can generally be observed in different plant parts. The accurate assessment of plant symptoms can be used as a proxy indicator for managing disease incidence, estimating yield loss, and developing genotypes with disease resistance. The objective of this work was to determine the response of the photosynthetic apparatus to the increased disease severity caused by web blight Thanatephorus cucumeris (Frank) Donk on the common bean (Phaseolus vulgaris L.) leaves under acidic soil and the humid tropical conditions of the Colombian Amazon. Differences in chlorophyll fluorescence parameters, including Fv/Fm, Y(II), Y(NPQ), Y(NO), ETR, qP, and qN in leaves with different levels of severity of web blight in an elite line (BFS 10) of common bean were evaluated under field conditions. A significant effect of web blight on the photosynthetic apparatus was found. A reduction of up to 50% of energy use dedicated to the photosynthetic machinery was observed, even at the severity scale score of 2 (5% surface incidence). The results from this study indicate that the use of fluorescence imaging not only allows for the quantifying of the impact of web blight on photosynthetic performance, but also for detecting the incidence of disease earlier, before severe symptoms occur on the leaves.